Evaluasi Parameter RAW Berdasarkan Multirate Pada IEEE 802.11ah: Simulasi Kinerja Optimum Jaringan IoT - Haris Mustaqin; Teuku Yuliar Arif; Rizal Munadi (Ikatan Ahli Informatika Indonesia (IAII), 2021)
IEEE 802.11ah WLAN is a technology standard for IoT networks because it can provide a higher transmission range and data rate than WPAN and LPWAN. To manage channel access up to 8191 at the MAC layer IEEE 802.11ah a Restricted Access Window scheme was introduced. Generally, evaluation and optimization of RAW parameters are only based on constant data rates without taking into account the mutirate support for PHY AP and STA IoT IEEE 802.11ah. This study uses an open source-based NS-3 network simulator. Simulation analysis is run by calculating the value of throughput, delay, packet loss, and energy consumption of each node. Based on testing the effect of the number of slots on throughput, it shows that the resulting throughput values ​​fluctuate with stable dominance, depending on the number of slots used. The effect of the number of slots on packet loss shows that the packet loss value is low for each slot because more packets can be accommodated in the RAW slot queue. The effect of the number of slots on energy consumption decreases at some data rates and some lower energy consumption values, thereby saving energy consumption.